Analysis of activator treatment changes - Hashim Hanizah Aman (Sciendo, 1991)
The effects of functional appliance treatment have been reported in numerous studies in the literature with great variability in the findings. It is generally agreed that they can be used successfully to treat Class II malocclusions in growing and cooperative patients. However, there is a lack' of consensus regarding the relative orthodontic and orthopedic correction obtained by functional appliances in Class II correction. Lateral cephalometric radiographs from a sample (n=36) of patients who had undergone a phase of treatment with activator appliances were measured and analysed for changes using a modified version of the method described by Johnston (Hashim and Godfrey 1990). In this method, the treatment changes were broken down into: tooth movement relative to basal bone; and the translatory growth of the jaws, both with respect to the cranial base and to each other. The results show that the treatment effects were mainly dentoalveolar. There was a slight orthopedic effect on the maxilla, but no significant mandibular growth was observed, above that which can be expected from normal growth.